2018
DOI: 10.2174/1568009617666170623120742
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti-cancer Activity of Stilbene and Methoxydibenzo[b,f] oxepin Derivatives

Abstract: Among the newly synthesized stilbene derivatives, we selected two as potent anticancer compounds triggering late apoptosis/necrosis in cancerous cells through sub-G1 phase cell cycle arrest. They changed cyclin expression, induced DNA repair mechanisms, enzymes involved in apoptosis and oxidative stress response. Compounds JJR5 and JJR6 can be a base for structure modification(s) to obtain even more active derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Continuing our study [25][26][27][28][29][30][31] of microtubule inhibitors, we analyzed the structure of active colchicine, active combretastatin A-4, and derivative dibenzo[b,f ]oxepine (Figure 1). It can be observed that the substituents and backbone arrangements were similar.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuing our study [25][26][27][28][29][30][31] of microtubule inhibitors, we analyzed the structure of active colchicine, active combretastatin A-4, and derivative dibenzo[b,f ]oxepine (Figure 1). It can be observed that the substituents and backbone arrangements were similar.…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed that the substituents and backbone arrangements were similar. Additionally, the dibenzo[b,f ]oxepine showed the strongest cytotoxic effect against HeLa and U87 cancerous cells [27] and had (Z)-stilbene motif in their skeleton. Additionally, their aromatic rings were connected by oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…[40][41][42] Newly discovered Res analogs and oligomers from diverse sources have exhibited more potent anticancer activity than Res itself. [43][44][45] Stilbenes' anticancer mechanisms result from the modulation of multiple signaling pathways, including cell cycle arrest, induction of DNA repair and stress response, apoptosis, and antiangiogenesis, [46][47][48] therefore justifying the anticancer resourcefulness of Res and its analogs and polymers. [49] Gnetin C (GnC) is a naturally occurring dimer of Res found in the melinjo plant Gnetum gnemon, which is widely farmed in Southeast Asia and used in Indonesian cuisine.…”
Section: Introductionmentioning
confidence: 99%
“…Dibenzo[b, f ]oxepine derivatives are an important scaffold in natural, medicinal chemistry, and these derivatives occur in several medicinally relevant plants [1][2][3]. The dibenzo [b, f ] oxepine system can be associated with various biological properties such as antidepressant and anti-estrogenic [4], analgesic [5], anti-inflammatory [6], antipsychotic [7], angiotensin II receptor antagonistic [8], antioxidant [9], antimycobacterial [10], antidiabetic [11], and antitumor activities [3,12], as well as anti-apoptosis [13] properties. The treatment of progressive neurodegenerative diseases [14] such as Parkinson's and Alzheimer's diseases [15] with synthetic dibenzo[b, f ]oxepine derivatives is of particular interest.…”
Section: Introductionmentioning
confidence: 99%